Work, family, and personal characteristics explain occupational and gender differences in work–family conflict among Japanese civil servants. (December 2017) - Koura, U.; Sekine, M.; Yamada, M.; Tatsuse, T.
Abstract: Objectives: A high level of work–family conflict (WFC) is an important risk factor for physical and mental health problems. Although individual work-related factors for WFC have been extensively studied, relatively little is known about whether occupation and gender affect WFC and how such effects might be generated. Study design: Cross-sectional study. Methods: This study surveyed 3053 civil servants aged 20–65 years working in a local government in the west coast of Japan in 2003. Logistic regression analyses were used to examine whether there are occupational and gender differences in WFC and to clarify the factors underlying these differences. Results: WFC was higher in professional and technical workers compared with other occupations for both men and women, with age-adjusted odds ratios (ORs) for these workers of 1.29 in men and 2.58 in women. In men, occupational differences in WFC disappeared after adjusting for work and family characteristics (OR = 1.15). In women, significant occupational differences remained in the final model, but after adjusting for work characteristics the adjusted OR for professional and technical workers was reduced to 1.69. Women were more likely than men to experience high WFC (OR = 2.52). After controlling for work characteristics, the gender difference was considerably reduced (OR = 1.68). Conclusions: Work characteristics play a fundamental role in the difference in WFC between not only occupational but also gender differences. Stressful work characteristics among professional and technical workers and among women in all work roles should be addressed to reduce occupational and gender differences in WFC in Japan. Highlights: Work–family conflict (WFC) was highest in the professional and technical workers. Women were more likely than men to experience high WFC. Shift work and high demand played a major role in the occupational difference. These work characteristics were also fundamental to the gender difference.